2005
DOI: 10.1152/ajpheart.00650.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic effects of heterozygous, homozygous, and compound heterozygote myosin heavy-chain mutations

Abstract: . Molecular and phenotypic effects of heterozygous, homozygous, and compound heterozygote myosin heavy-chain mutations. Am J Physiol Heart Circ Physiol 288: H1097-H1102, 2005. First published November 4, 2004 doi:10.1152/ajpheart.00650.2004.-Autosomal dominant familial hypertrophic cardiomyopathy (FHC) has variable penetrance and phenotype. Heterozygous mutations in MYH7 encoding ␤-myosin heavy chain are the most common causes of FHC, and we proposed that "enhanced" mutant actin-myosin function is the causati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 41 publications
5
38
0
Order By: Relevance
“…A few examples have been published recently, among them the k207q myh7 mutation, in which heterozygous individuals develop a hypertrophic phenotype but those with the homozygous variant (only 1 individual) develop a DCM-like phenotype. 9 Thus, the tni-203/mhc-403 mouse model supports the clinical observation that Ϸ5% of all individuals affected by FHC carry compound-and/or double-heterozygous mutations and exhibit a more severe phenotype.…”
Section: Article P 1820supporting
confidence: 60%
“…A few examples have been published recently, among them the k207q myh7 mutation, in which heterozygous individuals develop a hypertrophic phenotype but those with the homozygous variant (only 1 individual) develop a DCM-like phenotype. 9 Thus, the tni-203/mhc-403 mouse model supports the clinical observation that Ϸ5% of all individuals affected by FHC carry compound-and/or double-heterozygous mutations and exhibit a more severe phenotype.…”
Section: Article P 1820supporting
confidence: 60%
“…11,[39][40][41] Previously, isolated cases of digenic inheritance underlying diseases such as HCM have been identified by targeted Sanger sequencing of candidate genes, [6][7][8]42 but clearly, WES approaches now allow a comprehensive and systematic approach to questions of genetic modifiers and digenic inheritance. We therefore hypothesized that all family members affected by DCM would segregate an identical mutation, but that the severely affected persons could have an additional variant in the same or a second gene.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two or more sequence alterations present either in the same or in different genes were demonstrated to occur in 3-5% of cases of familial HCM, associated with a greater clinical severity of HCM. [6][7][8] Similarly, compound and digenic heterozygosity were identified in patients with arrhythmogenic right ventricular cardiomyopathy, whereby several desmosome and celljunction genes were found to carry more than one mutation likely associated with low penetrance. 9 It is to be expected that similar modifiers exist for DCM; even though a single case of a 14-year-old boy with manifestations of DCM and mutations in both MYH7 and TNNT2 has been published, 10 little is known about the genes and the molecular mechanisms involved in modifying the phenotype of familial DCM.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Recent studies identified numerous patients with cardiomyopathy who have more than 1 disease-causing mutation. [42][43][44] These mutations can occur in either the same gene (compound heterozygotes) or in different genes (double heterozygotes) in up to 5% of genetic cardiomyopathies. 45 As a consequence of these complex genotypes, the individual risk to develop end-stage disease or sudden cardiac death can strongly increase.…”
Section: Meder Et Al Diagnostic Next-generation Sequencing 119mentioning
confidence: 99%